Enhancement of design and planning process for residential area through 3D architectural modelling participatory design - Mohd Yunos, Mohd Yazid; Ibrahim, Rahinah; Ismail, Nor Atiah; Mohd Isa, Nor Kalsum (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Interactive participatory design in landscape design process in Malaysia is very momentous as its technique will support communities to bring about shape their residential. The paper is to examine the appropriate of interactive participatory technique namely as 3D Participatory Design that might enhance of neighbourhood design. Case study has been applied for this research strategy. A proposed site for staff quarters residential area in Universiti Putra Malaysia campus is selected. Direct observation has been used specifically to understand the continuing behaviour of the experts group and participants (local community), and the process and unfolding of the 3D participatory design exercise. The most contributions of this research are to accentuate the implementation of 3D Participatory Landscape Design in the urban landscape development process will help in achieving a sustainable community. The urban dwellers will become sensitive to their living environment and its technique recognised as a tool for achieving a better quality living for people.